The Influence of Incentives and Leadership Support on Employee Performance: Collectibility Target as a Mediation Variable - Hidayat, Wahyu; Tangisalu, Jannati; Hasbiyadi, Hasbiyadi (International Business Management - Universitas Ciputra, 2024)
This study aims to investigate the relationship between incentives and leadership support on employee performance, with a specific focus on the mediating role of collectability targets. The research was conducted at PT. KB Finansia Multi Finance Makassar Branch, involving 90 employees from the collection unit. The method employed Partial Least Squares (PLS) for data analysis to assess the direct and indirect effects of incentives and leadership support on employee performance. The results indicate that incentives negatively impact employee performance, while leadership support positively influences it. Additionally, both incentives and leadership support were found to positively affect collectability targets, which in turn, significantly improve employee performance. These findings highlight the critical role of strategic incentives and effective leadership in enhancing collectability targets and overall employee performance.